Effect of growth rate and pH on lithium incorporation in calcite. (1st March 2019) - Füger, A.; Konrad, F.; Leis, A.; Dietzel, M.; Mavromatis, V.
Abstract: Carbonates are only a minor sink of oceanic lithium, yet the presence of this element and its abundance relative to other metal cations in natural carbonate minerals is routinely used as a paleo-environmental proxy. To date, however, experimental studies on the influence of physicochemical parameters that may control lithium incorporation in calcite, like pH and precipitation rate, are scarce. Therefore, we experimentally studied Li incorporation in calcite to quantify the apparent partitioning coefficient ( D Li ∗ = c Li / c Ca calcite m Li + / m Ca 2 + solution ) between calcite and reactive fluid as a function of calcite growth rate and pH. The obtained results suggest that D Li ∗ increases with calcite growth rate, according to the expression: L o g D Li ∗ = 1.331 ( ± 0.116 ) × L o g R a t e + 6.371 ( ± 0.880 ) ( R 2 = 0.87 ; 10 - 8 . 1 ≤ R a t e ≤ 10 - 7 . 1 m o l m - 2 s - 1 ) Additionally the experimental results suggest that D Li ∗ values exhibit a strong pH dependence. For experiments conducted at similar growth rates (i.e. Rate = 10 −7.7±0.2 mol m −2 s −1 ), D Li ∗ decreases with increasing pH as described by: L o g D Li ∗ = - 0.57 ( ± 0.047 ) × p H + 0.759 ( ± 0.366 ) ( R 2 = 0.90 ; 6.3 < p H < 9.5 ) The positive correlation of D Li ∗ with calcite growth rate is consistent with an increasing entrapment of traces/impurities at rapidly growing calcite surfaces, although the incorporation of monovalent cations such as Li + and Na + does not necessarily imply a substitution of Ca 2+ ions in the calcite crystal lattice. The dependence of D Li ∗ on pH can be considered as an indication that activity of aqueous HCO3 − controls the incorporation of Li + in calcite. The proposed coupled reaction can be explained by charge balance of these monovalent species, which is likely valid at least during the initial step of adsorption on the crystal surface. These new findings shed light on the mechanisms controlling Li incorporation in calcite and have direct implications on the use of Li partitioning coefficients in natural carbonates as an environmental proxy.